Reconceptualizing Islamic Early Education through Foundational Arabic Literacy - Kabul Suprayitno; Ahmadi Ahmadi; Sanjaka Yekti; Nurhasma Muhamad Saad (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study reconceptualizes early childhood Islamic education by positioning fundamental Arabic literacy as a holistic framework that nurtures linguistic, moral, and spiritual development. Drawing on Islamic education and Vygotsky's sociocultural theory, the study employed a qualitative interpretive design involving classroom observations, interviews, and document analysis in three Islamic early childhood education institutions. The findings reveal that Arabic literacy serves not only as a medium for language acquisition but also as a channel for transmitting faith-based values ??and shaping children's moral reasoning. Through practices such as Quranic storytelling, ritual expressions, and dialogic interactions, Arabic becomes a mediating tool connecting cognition, emotion, and spirituality. Teachers play a central role as moral facilitators, guiding students to connect Arabic language learning with ethical reflection and emotional engagement. This study's novel contribution lies in reinterpreting Arabic literacy as spiritual literacy a transformative educational paradigm that integrates faith, language, and identity formation. Theoretically, it broadens the sociocultural perspective by incorporating spirituality into language learning, while practically, it offers a model for educators to cultivate spiritual awareness and moral consciousness through the teaching of basic Arabic in early Islamic education.